2017
DOI: 10.3892/etm.2017.5512
|View full text |Cite
|
Sign up to set email alerts
|

Geniposide attenuates epilepsy symptoms in a mouse model through the PI3K/Akt/GSK‑3β signaling pathway

Abstract: Abstract. Previous reports on the pharmacological actions of geniposide have indicated that it has anti-asthmatic, anti-inflammatory and analgesic effects in the liver and gallbladder, and therapeutic effects in neurological, cardiovascular and cerebrovascular diseases. The results of the current study demonstrate that geniposide attenuates epilepsy in a mouse model through the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/glycogen synthase kinase-3β (GSK-3β) signaling pathway. A mouse model of epile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…This study also explored the proteins involved in the PI3K/Akt/Nrf2/HO-1 pathway in the dynorphin-associated protection in epilepsy. Activation of the PI3K/Akt signaling pathway can alter neuronal apoptosis and attenuates the severity of seizures in experimental epilepsy-induced rats [20][21][22]. On the other hand, activation of the antioxidant Nrf2/ ARE pathway confers neuroprotective effects against pentylenetetrazole-or pilocarpine-induced brain damage in vivo and Mg 2+ free-induced seizure-like neuron injury [10,15,16,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also explored the proteins involved in the PI3K/Akt/Nrf2/HO-1 pathway in the dynorphin-associated protection in epilepsy. Activation of the PI3K/Akt signaling pathway can alter neuronal apoptosis and attenuates the severity of seizures in experimental epilepsy-induced rats [20][21][22]. On the other hand, activation of the antioxidant Nrf2/ ARE pathway confers neuroprotective effects against pentylenetetrazole-or pilocarpine-induced brain damage in vivo and Mg 2+ free-induced seizure-like neuron injury [10,15,16,19].…”
Section: Discussionmentioning
confidence: 99%
“…The phosphatidylinositol-3-kinase (PI3K)/Akt pathway is a key regulator of cell survival and proliferation that is widely expressed in the central nervous system. Activation of the PI3K/Akt signaling pathway can alter neuronal apoptosis and attenuate the severity of seizures in experimental epilepsy-induced rats [20][21][22]. Interestingly, Tong et al [23] have demonstrated that U50448H, a KOR-selective agonist, protects against heart failure following myocardial ischemia/reperfusion via activation of HO-1 expression through the PI3K/ Akt/Nrf2 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Geniposide, an iridoid glycoside in Gardenia jasminoides , exerts anti-fibrotic, anti-osteoarthritis, and anti-epilepsy actions by modulation of the expression of transforming growth factor-β (TGF-β)/Smad4, p38 mitogen-activated protein kinase (p38 MAPK), and PI3K/Akt/GSK-3beta signaling pathways, respectively [ 55 , 56 , 57 ]. Whereas, geniposide manifested a number of pathological phenomena in the liver of SD rat with the dose greater than 574 mg/kg, such as elevated MDA, liver enzymes (ALT, AST, alkaline phosphatase (ALP), total bilirubin), focal necrosis, and downregulated SOD, leading to the onset of oxidative stress caused hepatotoxicity [ 58 ].…”
Section: Molecular Mechanisms Involved In Tcm-induced Oxidative Hementioning
confidence: 99%
“…1C), and this revealed that Trem2 and Tyrobp were in core positions. Interestingly, previous studies have proposed that Trem2 plays an important role in epilepsy [22,23], and the PI3K/ Akt pathway has also been reported to be a crucial regulator in epilepsy [24][25][26]. Moreover, several studies have demonstrated a target relationship between Trem2 and the PI3K/Akt pathway [14,27], indicating that Trem2 could modulate the PI3K/Akt pathway as shown in Fig.…”
Section: Trem2 Has Potential To Protect Against Epilepsy Through the mentioning
confidence: 94%